Rural Cardiac Screening: Leveraging Technology from a Previously Established Echocardiographic Network: Rural Cardiac Screening - Johnson, Theresa; Skipper, Eric R.; Robicsek, Francis (Journal of Humanitarian Cardiovascular Medicine, 2022)
Objectives: The authors review the history of two cardiac programs in Guatemala and Belize that were initiated by the late Dr. Francis Robicsek. Building upon his legacy, the aim of the rural cardiac screening program is to further extend the reach to those individuals disenfranchised from cardiac services. Methods: Complementary to the Nan Van Every Cardiology Diagnostic Network, screening stations are organized once a year at two cardiac echo stations in Guatemala and two clinics in Belize. Demographic information and medical history are collected; limited physical and diagnostic tests performed; and results are reviewed by a cardiologist and relayed to the participant. Participants with a suspected heart issue are referred to one of the cardiology and cardiac programs in Guatemala or Belize for in-depth evaluation. Education on cardiovascular diseases, signs, symptoms, and risk factors is provided, as well as healthy lifestyle habits. Results: Building upon successful cardiac programs in low resource settings lends the ability to expand the cardiovascular screening and awareness reach. Heart disease is brought to the forefront in communities where there is no previously known access and clinicians are educated to identify heart problems. Conclusion: The success of Unidad de Cirugía Cardiovascular de Guatemala (UNICAR) in Guatemala City, and the cardiology and cardiac surgical programs at Karl Heusner Memorial Hospital Authority in Belize, and the Nan Van Every Cardiology Diagnostic Network, are the cornerstones to scaling the expansion and encounter individuals who have little, if any, knowledge about cardiac diseases, signs, symptoms and prevention.